2021
DOI: 10.1111/mms.12811
|View full text |Cite
|
Sign up to set email alerts
|

Diel and lunar variation in diving behavior of rough‐toothed dolphins (Steno bredanensis) off Kauaʻi, Hawaiʻi

Abstract: Observational studies describe rough‐toothed dolphins (Steno bredanensis) actively foraging during the day on epipelagic species. Using data from depth‐transmitting satellite tags deployed on nine individuals off Kauaʻi, we investigated diving behavior and the effects of lunar phase and solar light levels on vertical movements. Overall, tagged rough‐toothed dolphins primarily used near‐surface waters, spending between 83.6% and 93.7% of their time in the top 30 m of the water column. When diving, grand mean, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 52 publications
2
15
0
Order By: Relevance
“…Recently updated habitat-based density models for Hawaiian odontocetes suggest that the locations of the Kauaʻi and PHR HARPs are within predicted regions of highest density for the rough-toothed dolphin [ 52 ]. Preliminary exploration into diel trends in this type revealed an overwhelming decrease in acoustic activity during daylight hours, which fits with a recent study of rough-toothed dolphin diving behavior that has suggested the species is more active during dusk/night [ 53 ].…”
Section: Resultssupporting
confidence: 79%
“…Recently updated habitat-based density models for Hawaiian odontocetes suggest that the locations of the Kauaʻi and PHR HARPs are within predicted regions of highest density for the rough-toothed dolphin [ 52 ]. Preliminary exploration into diel trends in this type revealed an overwhelming decrease in acoustic activity during daylight hours, which fits with a recent study of rough-toothed dolphin diving behavior that has suggested the species is more active during dusk/night [ 53 ].…”
Section: Resultssupporting
confidence: 79%
“…The low sample size and beluga distribution during spring precluded robust conclusions regarding responses to the switch from polar night to the spring day/night cycle (although see Supplementary Material 2 for discussion); further targeted studies on the Arctic odontocetes, in particular the higher latitude narwhal populations, could address this question. Furthermore, the lunar cycle is known to influence diel behaviour in predators, which generally make deeper nighttime dives during a full moon related to prey depth or visibility (Owen et al, 2019, Shaff & Baird 2021). In the Arctic, the rising of the moon can disrupt DVM during late fall; and during the polar night, lunar vertical migration (LVM) of zooplankton can occur over several days centred around the full moon (Last et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Marine predators inhabiting mid to low latitudes frequently exhibit diel patterns in behaviour associated with relatively uniform day/night light cycles (e.g. Arranz et al, 2011, Madigan et al, 2021, Shaff & Baird 2021). The present study confirms the hypothesis that initiation of diel patterns in dive behaviour by a marine predator coincides with the switch from 24‐hour daylight to a daily light/dark cycle, as would be expected.…”
Section: Discussionmentioning
confidence: 99%
“…Presence in deeper waters close to continental shelves, are a frequently observed pattern, as nutrient rich upwellings can drive concentration of prey species (Shaff and Baird, 2021). Similarly, diurnal variation in activity and use of different depth zones, sometimes interacting with the lunar phase, has also been reported (Shaff and Baird, 2021). Increased use of surface waters (<20 m) by fin whales (Balaenoptera physalus) in the Southern California Bight at night has been observed (Keen et al, 2019).…”
Section: Cetofauna Detectionmentioning
confidence: 96%
“…Cetacean distributions are closely aligned with prey distributions. Presence in deeper waters close to continental shelves, are a frequently observed pattern, as nutrient rich upwellings can drive concentration of prey species (Shaff and Baird, 2021). Similarly, diurnal variation in activity and use of different depth zones, sometimes interacting with the lunar phase, has also been reported (Shaff and Baird, 2021).…”
Section: Cetofauna Detectionmentioning
confidence: 97%